Is fund performance driven by flows into connected funds? spillover effects in the mutual fund industry - Bing Zhu; René-Ojas Woltering (Journal of Economics and Finance, 2021)
Mutual funds are connected with each other through overlapping portfolio holdings. We document that the performance of individual mutual funds is affected by spillover effects from fund flows to connected mutual funds. Spillover-effects are particularly pronounced during crisis periods, when a one standard deviation increase in flows to the tercile of funds with the highest overlapping portfolio holdings is associated with a monthly excess returns of 1.50%. Small cap stock funds are more heavily impacted, suggesting that the spillover effect is related to underlying asset liquidity. Moreover, we shed light on the dark side of diversification, as highly diversified funds are more exposed to the spillover risk factor.
Keywords: G11; G14; G24; 330; Fund Flows; Price Pressure; Spillover Effects